Bilateral epididymal injury following trauma: An uncommon cause of obstructive infertility - Ahmed Ibrahimi; Adam El Aboudi; Salim Ouskri; Hamza El Abidi; Imad Boualaoui; El Sayegh Hachem; Nouini Yassine (Urology Case Reports)
Scrotal trauma, though uncommon, can rarely result in isolated epididymal injury, as seen in a rare case of bilateral epididymal injury leading to obstructive infertility in a 23-year-old male who sustained blunt scrotal trauma. Doppler ultrasound revealed bilateral hematocele and epididymal discontinuity, which was confirmed by surgical exploration showing bilateral epididymal lacerations. Postoperative semen analysis indicated azoospermia. Isolated epididymal injuries are rarely diagnosed early, emphasizing the importance of thorough imaging and consideration of fertility preservation. Urologists should consider early sperm preservation in cases with a high risk of infertility.